Analisis Penyelesaian Kasus Wanprestasi dalam Perjanjian Jual Beli Kios - Dian Anggi Rahayu; Elisabet Nauli Pane; Farchanza Haykanna Pireno; Samirah Novel; Widya Tri Lestari; Dwi Aryanti Ramadhani (Lembaga Pengembangan Kinerja Dosen, 2024)
An agreement is when a person commits to another person to do something or when both parties commit to carry out something. However, in practice, there are often cases of default, where there are parties who do not fulfill their obligations in accordance with the contents of the agreement, as happened in the case of a kiosk sale and purchase agreement in Kupang District Court Decision Number 132.18/PDT.G/2016/PN.KPG. This article aims to analyze the occurrence of default in the kiosk sale and purchase agreement and analyze the judge's decision in resolving the default with the principles of justice. This article adopts a qualitative approach by using the normative juridical method and conducting a literature study. The results of this research analysis explain that the judge's decision in this case has fulfilled the necessary conditions. The Defendant has been found in default by the Panel of Judges and is entitled to pay the remaining money according to the agreement letter. The principles of legal certainty and justice have also been applied properly by considering all evidence and witness testimony before making a decision.